Molecular phylogeny and historical biogeography of Cyclommatus stag beetles (Coleoptera: Lucanidae): Insights into their evolution and diversification in tropical and subtropical Asia - Zhu, Xue Li; Yuan, Jiao Jiao; Zhou, Li Yang; Bartolozzi, Luca; Wan, Xia (Frontiers in Ecology and Evolution, 2023)
Cyclommatus stag beetles (Coleoptera, Lucanidae) are very interesting insects, because of their striking allometry (mandibles can be longer that the whole body in large males of some species) and sexual dimorphism. They mainly inhabit tropical and subtropical forests in Asia. To date, there has been no molecular phylogenetic research on how these stag beetles evolved and diversified. In this study, we constructed the first phylogenetic relationship for Cyclommatus using multi-locus datasets. Analyses showed that Cyclommatus is monophyletic, being subdivided into two well-supported clades (A and B). The clade A includes the island species from Southeast Asia, and the clade B is formed by the continental species. The divergent time estimates showed these beetles split from the outgroup around 43.10 million years ago (Mya) in the late Eocene, divided during the late Oligocene (around 24.90 Mya) and diversified further during the early and middle Miocene (around 18.19 Mya, around 15.17 Mya). RASP analysis suggested that these beetles likely originated in the Philippine archipelago, then dispersed to the other Southeast Asian archipelagoes, Indochina Peninsula, Southeast Himalayas, and Southern China. Moreover, relatively large genetic distance and stable morphological variations signified that the two clades reach the level of inter-generic differences, i.e., the current Cyclommatus should be separated in two genera: Cyclommatus Parry, 1863 including the clade A species, and Cyclommatinus Didier, 1927 covering the clade B species. In addition, the evidence we generated indicated these beetles’ diversification was promoted probably by both long-distance dispersal and colonization, supporting an “Upstream” colonization hypothesis. Our study provides insights into the classification, genetics and evolution of stag beetles in the Oriental region.